Patients Preferences in Breaking Bad News: A Cross-Sectional Study - Nader, Israa H.; Hasan, Lamyaa A.; Al-Naqqash, Manwar A.; Tahir, Saad D. (Journal of the Faculty of Medicine Baghdad, 2025)
Background: Doctors and patients communicating effectively is a very important base in cancer clinics and out-patient, the “Bad” news is any information that drastically alters a patient’s prospect of their life and forthcoming possibilities. It includes facts about diagnosis, recurrence, and treatment failure in clinical oncology settings. Objective: To assess the attitudes of cancer patients toward receiving bad news of their condition and the relationships of some sociodemographic variables to these attitudes. Methods: A cross-sectional study was conducted from the 19th of February to the 1st of June 2017 at the Oncology Hospital in the Medical City Teaching Centre/Baghdad. A group of 212 cases completed the questionnaire, which included socio-demographic information (age, gender, marital status, occupation, and education). The preference and attitude questions were set as in the recommended steps of the SPIKES protocol, which is a six-part method for sharing bad news with patients (Setting, Perception, Invitation, Knowledge, Emotions, and Summary). Result: Patients were classified into two age groups: those 50 years or older (64.2%) and those below 50 years (35.8%). Of the 212 cases, 46.2% were housewives, and 20.8% were government employees. The majority of patients (80.2%) preferred to be informed about their disease, its type, its prognosis, treatment, and life expectancy on the first visit. Most of the participants (67.9%) thought that the most experienced and skilled doctors have to notify them completely about their medical condition. The majority of them (81.1%) preferred that the physician use the word (disease) instead of "cancer. Most patients (75.5%) thought that it is better to train healthcare professionals in communication skills and how to break bad news. Conclusion: Patients diagnosed with cancer are willing to learn about the diagnosis and are keen to receive details as early as possible about its type and prognosis, treatment, and life expectancy.